2015
DOI: 10.5487/tr.2015.31.2.151
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial-mesenchymal Transition is Associated with Acquired Resistance to 5-Fluorocuracil in HT-29 Colon Cancer Cells

Abstract: 5-Fluorouracil (5-FU) is commonly used for the therapy of colon cancer; however, acquired resistance to 5-FU is a critical barrier to successful treatment and the primary cause of chemotherapy failure. Epithelialmesenchymal transition (EMT) is a process whereby cells undergo alterations in morphology and molecular characteristics promoting tumor progression and metastasis. Accumulating evidence shows that transition from epithelial to mesenchymal phenotype in cancer cells is associated with their resistance to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 28 publications
4
36
0
Order By: Relevance
“…We showed that an EMT signature consisting of nuclear β-catenin, down-regulated E-cadherin and overexpression of ZEB and Snail is associated with invasion, metastasis and chemoresistance in human CRC. We also report for the first time that ZEB expression in our cohort of metastatic CRC is an independent predictor of poor response to chemotherapy and, in agreement with recent studies, we demonstrate that 5-FU resistant HT29 cells show features of EMT (41,42). Consistently, several lines of evidence indicate multiple interactions between E-cadherin, Wnt/β-catenin and the EMT key transcription factors Snail and ZEB inducing an invasive mesenchymal phenotype of epithelial cells in CRC (43)(44)(45)(46)(47).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We showed that an EMT signature consisting of nuclear β-catenin, down-regulated E-cadherin and overexpression of ZEB and Snail is associated with invasion, metastasis and chemoresistance in human CRC. We also report for the first time that ZEB expression in our cohort of metastatic CRC is an independent predictor of poor response to chemotherapy and, in agreement with recent studies, we demonstrate that 5-FU resistant HT29 cells show features of EMT (41,42). Consistently, several lines of evidence indicate multiple interactions between E-cadherin, Wnt/β-catenin and the EMT key transcription factors Snail and ZEB inducing an invasive mesenchymal phenotype of epithelial cells in CRC (43)(44)(45)(46)(47).…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with previous studies 5-FUR cells show morphologic changes by light microscopy consistent with EMT, as well as, an EMT and CSC related expression profile by immunoblotting i.e. decreased levels of the epithelial marker E-cadherin, increased expression of active β-catenin and mesenchymal markers vimentin and Snail and increased levels of the CSC marker Lgr5 ( Figure 5) (41,42). However similar EMT changes were not observed in OxalR cells (data not shown).…”
Section: Expression Of Ilk E-cadherin Zeb and Cd44 In Metastatic supporting
confidence: 91%
See 1 more Smart Citation
“…Recent research has demonstrated that epithelial-to-mesenchymal transition (EMT) plays a key role in the early process of metastasis of cancer cells [5,6]. During the acquisition of EMT characteristics, cancer cells lose the expression of genes that promote cell-cell contact, such as E-cadherin and the miR-200 family, and gain the expression of mesenchymal markers, such as vimentin, fibronectin and N-cadherin, leading to enhance cancer cell migration and invasion [7,8] and to confer drug resistance [9]. Therefore, the development of EMT inhibitors may provide novel strategies for the prevention, diagnosis and treatment of cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence suggests a direct molecular and phenotypic correlation between acquisition of EMT characteristics and chemoresistance in tumor cells [4,5]. In previous studies, it has been reported that EMT plays a role in the chemoresistance of human tumor cells in contrast to conventional therapeutics in chemotherapeutic drugs such as 5-FU and paclitaxel or molecular target drugs such as epidermal growth factor receptor (EGFR)-targeted agents [6][7][8]. Understanding the involvement of EMT in CDDP chemoresistance and the underlying mechanisms is of great interest to develop therapeutic avenues for the treatment of CDDP-resistant patients with advanced ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%